Mosquito bed net use and associated factors among pregnant women in Rwanda: a nationwide survey - Joseph Kawuki; Elorm Donkor; Ghislaine Gatasi; Lilian Nuwabaine (BMC Pregnancy and Childbirth, 2023)
Abstract Background In malaria-endemic countries such as Rwanda, the appropriate use of mosquito bed nets is an effective intervention for malaria prevention. Despite being one of the demographics most impacted by malaria, there is a dearth of literature on the usage of mosquito bed nets by pregnant women in Rwanda. The study aimed to assess the prevalence and associated factors for mosquito bed net use among pregnant women in Rwanda. Methods We used weighted data from the 2020 Rwanda Demographic and Health Survey of 870 pregnant women, and multistage stratified sampling was used to select participants. Multivariable logistic regression was conducted to determine the factors associated with mosquito bed net use, using SPSS (version 26). Results Of the 870 pregnant women, 57.9% (95%CI: 54.6–61.1) used mosquito bed nets. However, 16.7% did not use bed nets among those owning bed nets. On one hand, older age (AOR = 1.59, 95%CI: 1.04–2.44), primary education (AOR = 1.18, 95%CI: 1.07–2.23), being married (AOR = 2.17, 95%CI: 1.43–3.20), being from Kigali region (AOR = 1.97, 95%CI: 1.19–3.91), partner’s education (AOR = 1.22, 95%CI: 1.13–3.41), having recently visited a health facility (AOR = 2.07, 95%CI: 1.35–3.18), and being in the third pregnancy trimester (AOR = 2.14, 95%CI: 1.44–3.18) were positively associated with mosquito bed net use. On the other hand, low wealth index (AOR = 0.13, 95%CI: 0.07–0.24), and being from Eastern region (AOR = 0.42, 95% CI: 0.26–0.66) had a negative association. Conclusions About half of the pregnant women in Rwanda used mosquito bed nets and the usage was associated with various socio-demographics. There is a need for appropriate risk communication and continuous sensitisation to improve mosquito net use among pregnant women. Early antenatal care attendance and partner engagement in malaria prevention and mosquito net use, as well as consideration of household dynamics, are also crucial in improving not only mosquito net coverage but also utilization.